Sustainable food systems for food security Need for combination of local and global approaches - Thomas, Alban; Alpha, Arlène; Barczak, Aleksandra; Zakhia-Rozis, Nadine (éditions Quae, 2022)
Food and nutritional security refers to the challenge of providing sustainable, healthy and accessible food to all people. It has four interconnected dimensions: availability, access, utilization and stability. Tackling this tremendous challenge means transforming our food systems and mobilizing key stakeholders and decision-makers to leverage intersectoral knowledge and scientific evidence. From 2014 to 2020, CIRAD and INRAE led an ambitious interdisciplinary flagship programme on the transitions for global food security called GloFoodS. Authored by principal investigators and contributors to research projects funded by GloFoodS, this book is representative of the programme's interdisciplinary research but does not claim to provide exhaustive coverage of topics and approaches of food security. It presents recent research findings from many disciplines, including the life, engineering and social sciences. The findings were drawn from different analysis scales as well as from the combination of local and global food security approaches. The various chapters explore issues such as food system governance, balance and discrepancies between agricultural supply and food needs, the role of innovations in providing high-quality foods and promoting resilient value chains, and the role of local resource management in achieving food security. This book will be of interest to a broad scientific audience of researchers, academics, food systems professionals and decision-makers, as well as readers interested in food and nutritional security issues. Découvrez aussi sur notre boutique en ligne